1997
DOI: 10.1074/jbc.272.35.21938
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Oxygen Produced by Photodynamic Action Causes Inactivation of the Mitochondrial Permeability Transition Pore

Abstract: We have studied the effects of singlet oxygen produced by photodynamic action on the cyclosporin A-sensitive permeability transition (PT) in isolated rat liver mitochondria. Mitochondria were incubated with 3 M hematoporphyrin and irradiated at 365 nm with a fluence rate of 25 watts/m 2 . For short durations of irradiation (60 s) the adenine nucleotide translocase was inactivated, but mitochondria retained their ability to form a proton electrochemical gradient and accumulated Ca 2؉ and P i at the same rate as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 32 publications
4
44
0
Order By: Relevance
“…Thus, it seems that the loss of DW m is responsible for the AIF translocation, whereas the release of cytochrome c is not strictly dependent on DW m (37)(38)(39). Recent studies have suggested that the components of the permeability transition pore work together with proteins of Bcl-2 family to control the permeability transition pore opening in a specific manner for the release of mitochondrial proapoptotic proteins (39)(40)(41)(42). Two sites that help control the permeability transition pore have been proposed, the S and the P sites (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it seems that the loss of DW m is responsible for the AIF translocation, whereas the release of cytochrome c is not strictly dependent on DW m (37)(38)(39). Recent studies have suggested that the components of the permeability transition pore work together with proteins of Bcl-2 family to control the permeability transition pore opening in a specific manner for the release of mitochondrial proapoptotic proteins (39)(40)(41)(42). Two sites that help control the permeability transition pore have been proposed, the S and the P sites (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Two sites that help control the permeability transition pore have been proposed, the S and the P sites (40)(41)(42). The S site, which is cyclosporin A or bongkrekic acid sensitive (41), is responsible for the release of AIF, whereas the P site, which is cyclosporine A insensitive, is involved in the release of cytochrome c.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of Ca# + uptake is obtained after the collapse of the electric field built up by respiratory chain proton pumps or ATP hydrolysis. However, it has been reported [6,37] that photodamage of the electron transport chain is not a primary event after photodynamic action. Irradiation with increasing doses of light in the presence of HP produces first an inhibition of oxidative phosphorylation followed by an inhibition of Ca# + uptake and finally an arrest of respiration.…”
Section: Discussionmentioning
confidence: 99%
“…EVects on the bioenergetics, (Atlante et al 1989;Moreno 1981, 1990) primarily on the mitochondrial permeability transition pore (Salet et al 1997) have been investigated in detail (Dummin et al 1997;Morgan and OseroV 2001;Plaetzer et al 2002). PDT may induce permeabilization of both mitochondrial membranes, dissipation of the transmembrane potential, and a release of apoptosis-related proteins (such as cytochrome c, apoptosis inducing factor, second mitochondria derived activator of caspases and certain procaspases) into the intermembrane space (Almeida et al 2004;Oleinick et al 2002).…”
Section: Mechanisms Of Cell Death As a Function Of Subcellular Localimentioning
confidence: 99%